The Foundations of Italian Internal Politics under the International Changes 1918-1922 Historical study (Journal of the College of Basic Education, 2022)
This research deals with an important phase of the history of Italy have had the greatest impact in shaping the political future of Italy during subsequent years, through the spread of political and economic crises and the growth of socialist ideas and left-wing extremist of the emergence of socialist and communist parties, then fascism and seizing power in Italy, taking advantage of the conditions that prevailed in the that stage, the bad effects caused by the first World War for the Italians, and the disappointment allies who disclaiming for their promises to the Italian government stipulated by the Treaty of London secret 1915 that reflected this negatively on the internal situation, and coincided with the economic crises suffered by the government because of the war, and he exploited the communists the opportunity to take control of the factories and the organization of labor strike which led to the direction of the owners of factories to support the fascists who had their backs beginning of a phase of the dictatorship singles after the arrival of the leader of the fascist Party, Mussolini to power in 1922, was not limited to the impact of the emergence of fascists on Italy alone, but included all of the world through the involvement of the world later in the Second World War, which was the Fascists of the main parties.